SoltarinE: A Revolutionary Eco-Friendly Charging Station to Reduce Carbon Gases in PLN's Power Usage - Chika hayya Sabillah; Dhimas Agung Dwiputra; Aura Kharina (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The main goal of this study is to develop charging stations that use solar energy as an environmentally friendly alternative, in order to reduce carbon dioxide gas emissions produced from burning fossil fuels. The method used is qualitative with data collection through system observation and analysis of solar panel performance with dual-axis technology that can follow the movement of the sun. The results of the study show that the use of solar panels equipped with dual-axis actuators can increase the efficiency of sunlight absorption, so that the power produced is more optimal. From the analysis, it was found that these stations not only provide an efficient charging solution, but also contribute to a reduction in carbon footprint, with the potential for significant reductions in CO2 emissions. The conclusion of this study shows that the development of solar energy-based charging station technology is a strategic step in supporting the transition to a more sustainable energy source in Indonesia.